2019
DOI: 10.1111/jpn.13171
|View full text |Cite
|
Sign up to set email alerts
|

Water extract of Artemisia ordosica enhances antioxidant capability and immune response without affecting growth performance in weanling piglets

Abstract: The present experiment was conducted to investigate the effects of water extract of Artemisia ordosica (WEAO) on growth performance, antioxidant capability and immune response in weanling piglets. Seventy‐two 28‐day‐old weanling piglets were randomly allocated into four treatments with six replicate pens per treatment and three piglets per pen (n = 18). These four treatment diets were formulated by adding 0, 250, 500 and 750 mg/kg WEAO to the basal diet. The experiment lasted for 28 days. Body weight and feed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Liu et al (5) found that dietary plant extract (natural capsicum extracts) improved growth performance, immune and antioxidative functions of broilers, and suggested that the extract could be used as an effective alternative to antibiotics in broilers. It is worth noting that Artemisia plant extracts are rich in a variety of bioactive constituents, which can promote the growth, immune function, and antioxidant capacity of broilers (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al (5) found that dietary plant extract (natural capsicum extracts) improved growth performance, immune and antioxidative functions of broilers, and suggested that the extract could be used as an effective alternative to antibiotics in broilers. It is worth noting that Artemisia plant extracts are rich in a variety of bioactive constituents, which can promote the growth, immune function, and antioxidant capacity of broilers (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…[ 18 ]. In addition, owing to their high nutritional value and abundance of flavonoids [ 19 ], terpenoids [ 20 ], polysaccharides [ 21 ], sterols [ 22 ], coumarins [ 23 ], acetylenes [ 24 ], and other bioactive compositions, mainly flavonoid and terpenoid compounds [ 25 , 26 , 27 , 28 , 29 ], A. ordosica and their extracts have multiple pharmacological activities, including antimicrobial [ 30 ], antioxidative [ 31 ], anti-inflammatory [ 32 ], immunomodulatory [ 33 ], and, therefore, can be efficiently applied in poultry and animal production to promote health. Our previous studies have verified that A. ordosica aqueous extracts, mainly comprised of flavonoids, terpenoids, organic acids, and polysaccharides, could effectively improve the growth and antioxidant capacity of broilers and weanling piglets [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study demonstrated the growth promoting and immune regulatory effect of water extracts from Artemisia ordosica on broilers and piglets. 2,3 However, the specic compounds of Artemisia ordosica water extracts that have the anti-inammatory and antioxidant effect remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…It has shown that the gut microbiota plays a critical role in nutrient uptake, utilization, and metabolism, which may contribute to metabolic diseases. [10][11][12] Hence, based on our previous study of Artemisia ordosica in animals 2,3 and the ndings of other researchers, we hypothesized that Artemisia ordosica polysaccharide (AOP) in diets could affect antioxidative capacity and gut microbiota in animals and further exploration is imperative. The objective of this study was to investigate the optimized extraction conditions of AOP.…”
Section: Introductionmentioning
confidence: 99%